Restoration of the Severely Decayed Tooth Using Crown Lengthening with Simultaneous Tooth-Preparation - Park, Jun-Beom (European Journal of Dentistry, 2010)
This clinical case describes a treatment approach that combines, in a single appointment, a crown lengthening procedure and the final crown preparation for the restoration of a severely decayed tooth. This approach allows for a more accurate placement of the crown margin in relation to the bone crest while reducing treatment time. (Eur J Dent 2010;4:197-201)
Keywords: Periodontal surgery; Crown; Margin